Population and spectrum of droplets produced during electrostatic spraying and hydraulic spraying using air assistance - Baesso, Murilo Mesquita; Rofrigues Junior, Francelino Augusto; Magno Junior, Ronaldo Goulart; Teixeira, Mauri Martins; Modolo, Alcir Jose (Engenharia na Agricultura, 2014)
The droplet population produced during spraying influences the efficiency of pesticide application. It is possible to define a minimum number of droplets per unit area depending on the treatment and product to be applied. This study aimed to evaluate the characteristics of the populations and the spectra of droplets produced during electrostatic and air-assisted spraying. Factors including types of nozzles, spray volume, type of spray and its influence on the percentage coverage and density of droplet population. The experiment was arranged in a 2 x 2 x 2 factorial [two types of nozzles (Jacto JA-4, hollow cone and Jacto AXI-110-04, flat fan nozzle tip), two spray volumes (200 L ha -1 and 400 L ha -1 ) and two sprayer types (air-assistance in the spraying sleeve boom and electrostatic spraying)] in a randomized block design with four replications. The electrostatic sprayer increased droplet density per cm 2 of leaf.

A população de gotas produzidas durante a pulverização influencia a eficiência da aplicação de um fitossanitário. De acordo com o tratamento e o produto a ser aplicado, é possível definir um número mínimo de gotas por unidade de superfície. Este trabalho teve por objetivo avaliar as características das populações e o espectro das gotas produzidas durante a pulverização com assistência de ar e eletrostática. Foram estudados os fatores tipo de ponta, volume de calda aplicado, tipo de pulverizador e sua influência sobre porcentagem de cobertura e densidade da população de gotas. Foi conduzido um experimento em esquema fatorial 2 x 2 x 2:, sendo dois tipos de ponta (jato cônico vazio, modelo JA- 4, marca Jacto e jato leque, modelo AXI-110-04, marca Jacto), dois volumes de calda (200 e 400 L ha -1 ) e dois tipos de pulverizador (com assistência de ar na barra e pulverização eletrostática). Foi usado o delineamento de blocos ao acaso, com quatro repetições. A pulverização eletrostática aumentou a densidade de gotas por cm 2 de folha.
Keywords: Nozzle tip; Water-sensitive card and spray volume